Legislative bargaining with private information: a comparison of majority and unanimity rule - Piazolo, David; Vanberg, Christoph (AWI discussion paper series, 2024)
We present a three-person, two-period bargaining game with private information. A single proposer is seeking to secure agreement to a proposal under either majority or unanimity rule. If the first period proposal fails, the game ends immediately with an exogenously given "breakdown" probability. Two responders have privately known disagreement payoffs. We characterize Bayesian equilibria in stagewise undominated strategies. Our central result is that responders have a signaling incentive to vote "no" on the first proposal under unanimity rule, whereas no such incentive exists under majority rule. The reason is that being perceived as a "high breakdown value type" is advantageous under unanimity rule, but disadvantageous under majority rule. As a consequence, responders are "more expensive" under unanimity rule and disagreement is more likely. These results confirm intuitions that have been stated informally before and in addition yield deeper insights into the underlying incentives and what they imply for optimal behavior in bargaining with private information.
Keywords: Graue Literatur